Phase development and dielectric properties of 0.98BaTiO 3-0.02Ba(Mg1/3Nb2/3)O3 ceramic - Roongtao R. (2014)
The 0.98BaTiO3-0.02Ba(Mg1/3Nb2/3)O 3ceramics has been synthesized through a conventional mixed-oxide by using BT nanopowder and BMN micropowder. The phase purity of the powders and the ceramics was examined using X-ray diffraction (XRD). The 0.98BT-0.02BMN powders were sintered to 92% of the theoretical density at a temperature of 1300 °C for 2 h. The microstructure of the sintered surface was investigated using scanning electron microscopy (SEM). The dielectric constant (εr) and loss factor (tanδ) of the sintered pellets at Curie temperture were 3000 and 0.015, respectively. © (2012) Trans Tech Publications, Switzerland.